2018
DOI: 10.1016/j.jad.2018.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive negative thinking as a predictor of depression and anxiety: A longitudinal cohort study

Abstract: Repetitive Negative Thinking (RNT) is assumed to be a transdiagnostic proximal risk factor in depression and anxiety. We examined the prospective relations of disorder-dependent as well as disorder-independent measures of RNT with depression and anxiety outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
97
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(109 citation statements)
references
References 50 publications
8
97
2
2
Order By: Relevance
“…In order to assess RNT transdiagnostically, it therefore appears important to include items assessing the process of RNT. Of note, studies examining the differences between content-related versus process-related trait questionnaires regarding their predictive utility for depression and anxiety showed that an underlying RNT factor explained more variance in predicting anxiety and depression than disorder-specific cognitive content (i.e., rumination or worry) [65]. It remains to be tested whether the same applies to RNT assessed via EMA.…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess RNT transdiagnostically, it therefore appears important to include items assessing the process of RNT. Of note, studies examining the differences between content-related versus process-related trait questionnaires regarding their predictive utility for depression and anxiety showed that an underlying RNT factor explained more variance in predicting anxiety and depression than disorder-specific cognitive content (i.e., rumination or worry) [65]. It remains to be tested whether the same applies to RNT assessed via EMA.…”
Section: Discussionmentioning
confidence: 99%
“…Severity of depressive symptoms (last week) was assessed by means of the 30-item Inventory for Depressive Symptomatology (IDS) questionnaire [31] and used as a continuous variable. Internal consistency of the IDS in NESDA was previously found to be good (Cronbach's α = 0.91) [32]. Severity of anxiety symptoms (last week) was assessed by means of the 21-item Beck Anxiety Inventory (BAI), [33], also used as a continuous variable.…”
Section: Depression and Anxiety Diagnosesmentioning
confidence: 99%
“…Increasing evidence supports RNT as a style of thinking that operates across different mental health disorders (i.e., a transdiagnostic process) (18) that have been associated with an increased vulnerability to dementia and cognitive decline (19). For instance, RNT contributes to the development and maintenance of depression, anxiety, and post-traumatic stress disorder (20)(21)(22), all of which have been associated with cognitive decline and increased vulnerability to dementia (e.g., 16,23,24). It is possible that the increased risk of dementia conferred by these mental health disorders may be driven by RNT.…”
Section: Introductionmentioning
confidence: 99%